A 1-V 2.69-ppm/°C 0.8-μW bandgap reference with piecewise exponential curvature compensation. (March 2022) - Luo, Hongrui; Dong, Lei; Wang, Yuwei; Jiao, Zihao; Chen, Yang; Wang, Xiaofei; Zhang, Hong
Abstract: This paper presents a low-power precision bandgap reference (BGR) circuit consisting of a current-mode BGR core with piecewise exponential curvature compensation (PECC). Three differential MOS pairs operating in sub-threshold region are combined to generate the piecewise exponential current injecting into the BGR core for curvature compensation, while the voltages with different temperature dependence for three differential pairs are generated in turn from the BGR core. Together with the intrinsic first-order compensation, the proposed scheme actually realizes a 4th-order curvature compensated BGR. The current-mode structure permits the circuit's operation under sub-1V power supply. Fabricated in a 0.18-μm CMOS process, measured results for 88 samples show that the BGR achieves an average temperature coefficient of 2.69 ppm/°C (1.39 ppm/°C–8.6 ppm/°C) in the range of −40 to 125 °C after trimming. The measured line sensitivity is 0.03%/V in the supply range from 1 to 2.5 V. The current consumption is only 0.8 μA under a 1-V supply and the active area is 0.115 mm 2 .